Criminal Responsibility for Public Order Violations in Bandar Lampung (Study of Decision Number 8/Pid.C/2025/PN. Tjk) - Yafi Mahardika; I Ketut Seregig; Lukmanul Hakim (CV. Rayyan Dwi Bharata, 2026)
Public order violations are a common problem in urban areas and have the potential to disrupt public peace and comfort. This situation demands strict law enforcement, especially in determining the form of criminal liability for perpetrators of violations. In Bandar Lampung City, public order violations are specifically regulated in Bandar Lampung City Regional Regulation Number 01 of 2018 concerning Public Peace and Public Order. This study aims to determine and analyze the form of criminal liability for public order violations in Bandar Lampung City and examine the basis for judges' considerations in issuing decisions against perpetrators of these violations. The focus of the research is directed at the Tanjung Karang District Court Decision Number 8/Pid.C/2025/PN Tjk as a case study, to observe the application of criminal law in judicial practice for minor crimes that disturb public order. The research method used is a normative juridical method supported by an empirical approach. The results of the research are in Decision Number 8/Pid.C/2025/PN. The TJK shows that the defendant was legally and convincingly proven to have violated Article 59 letter a of Bandar Lampung City Regional Regulation Number 01 of 2018, and was sentenced to imprisonment with a probationary period. The sentence reflects an educational and preventive law enforcement effort. The judge's considerations in issuing the verdict were not only based on the legal aspects, but also considered sociological and philosophical aspects, such as the social impact of the act, the defendant's condition, and the purpose of the sentence. This study concludes that the judge's verdict has reflected the proportional and just application of the law, while still paying attention to the interests of society and humanitarian values in criminal law enforcement.